مقصد التیسیر في الشریعة الإسلامیة وأثره في المعاملات المالیة المعاصرة - نماذج مختارة - عبد اللاوي, حكیمة (University of Eloued-جامعة الوادي, 2015)
1 - Summary in the Englishlanguag This research deals with the purpose of easing in Islamic law and its impact on contemporary financial transactions - Selected models - where is the research topic of topics important Alvgahahalmqasidihaljd, and upon which the industrious and al-Faqih .and the mufti in the development of the provisions of the calamity The main objective of this study Hubean Samaha Islamic law and Rvgaha Balebad.okon facilitation feature of Islamic law and the intent of the general purposes, Fastmd Thread importance of the importance of intention, so as to attachment of guarding against evil and bring interests preserved public order, which is over the purpose .of the street from the legislation provisions Where was this work within two chapters: Chapter One: is a theoretical study for each of the Almqasdoaltesar. The second: it is a practical side to the subject, where the issues addressed in the contemporary financial transactions, I knew the subject matter, according to the sayings of scholars and the Holtbaan face .facilitation The conclusion: the stated range of findings through her .research
مذكرة ماستر
Keywords: مقصد التیسیر/الشریعة الإسلامیة/المعاملات المالیة; The purpose of facilitation/Islamic law/financial transactions